Photoresponsive ionic liquid crystals based on azobenzene guanidinium salts. Issue 13 (24th December 2014) - Wuckert, Eugen; Harjung, Marc D.; Kapernaum, Nadia; Mueller, Carsten; Frey, Wolfgang; Baro, Angelika; Giesselmann, Frank; Laschat, Sabine
Abstract : The mesomorphic properties and the kinetics of the E / Z -photoisomerization in an ILC matrix of new azobenzene ILCs were investigated. Abstract : The use of non-ionic LC phases as anisotropic matrices for E / Z -isomerization of azo-guest molecules is often restricted due to limited solubilities and demixing effects. In this study we therefore employed an ionic liquid crystal (ILC) matrix to follow the photo-induced E / Z -isomerization of ionic mesogenic azobenzene guanidinium guests. The latter were prepared from 4-hydroxy-4′-(octyloxy)azobenzene, which was first treated with N -(bromoalkyl)phthalimides to introduce the spacer with varying chain length. Removal of phthalimide and final reaction with a formamidinium salt linked the ionic head group to the photoisomerizable azobenzene unit. Investigation of the mesomorphic behaviour revealed for all azobenzene ILCs smectic A mesophases with high translational order parameters and partial bilayers, as could be stated by layer spacing d . Similar packing behaviour was found for the solid state by X-ray crystal structure analysis. E / Z -isomerization of azobenzene ILCs which were completely miscible with the ionic LC phase of C12 MIM-Br as anisotropic host was induced by irradiation with UV light and the reisomerization observed by time-resolved UV-Vis spectroscopy. For comparison, water was used as isotropic host. Z / E -reisomerization activation energies exhibited similar values of 97–100 kJ mol −1 irrespective of spacer lengths and the type of host. The results demonstrate that a proper match of steric requirements of host and guest as well as layer spacings are needed for a decreased activation energy.